Community empowerment for Tourism Village development in Sumberjaya Village, Choreutid District, Ciamis Regency - Willya Achmad (Trigin Publisher, 2023)
Tourism villages are driving the tourism economy and the people's economy, especially in rural areas. But to become a tourist village, it takes the potential and readiness of the community to be able to develop it. This research focuses on community empowerment strategies through the Development of the Sumberjaya Tourism Village, Cihaurbeuti District, Ciamis Regency. The method used by the author is descriptive method with a qualitative approach, data collection techniques by means of observation, interviews, and literature review analysis. The results of the study show that Sumberjaya Village, Cihaurbeuti District, Ciamis Regency has great potential to be developed into a sustainable national tourism village. However, the role of the community through empowerment in the development of the Sumberjaya tourism village is still very minimal so that it has not been able to take advantage of opportunities optimally. The active participation of the whole community is needed in the overall development of a tourist village in Sumberjaya Village.